Relationship between fine particulate air pollution and ischaemic heart disease morbidity and mortality. Issue 4 (23rd October 2014) - Xie, Wuxiang; Li, Gang; Zhao, Dong; Xie, Xueqin; Wei, Zaihua; Wang, Wei; Wang, Miao; Li, Guoxing; Liu, Wanru; Sun, Jiayi; Jia, Zhangrong; Zhang, Qian; et al.
Abstract : Objective: To assess the relationship between fine particulate matter (PM2.5 ) concentration and ischaemic heart disease (IHD) morbidity and mortality. Methods: A time-series study conducted in Beijing from 1 January 2010 to 31 December 2012. Data on 369 469 IHD cases and 53 247 IHD deaths were collected by the Beijing Monitoring System for Cardiovascular Diseases, which covers all hospital admissions and deaths from IHD from Beijing's population of 19.61 million. Results: The mean daily PM2.5 concentration was 96.2 μg/m 3 with a range from 3.9 to 493.9 μg/m 3 . Only 15.3% of the daily PM2.5 concentrations achieved WHO Air Quality Guidelines target (25 μg/m 3 ) in the study period. The dose–response relationships between PM2.5 and IHD morbidity and mortality were non-linear, with a steeper dose–response function at lower concentrations and a shallower response at higher concentrations. A 10 μg/m 3 increase in PM2.5 was associated with a 0.27% (95% CI 0.21 to 0.33%, p<2.00×10 −16 ) increase in IHD morbidity and a 0.25% (95% CI 0.10 to 0.40%, p=1.15×10 −3 ) increase in mortality on the same day. During the 3 years, there were 7703 cases and 1475 deaths advanced by PM2.5 pollution over expected rates if daily levels had not exceeded the WHO target. Conclusions: PM2.5 concentration was significantly associated with IHD morbidity and mortality in Beijing. Our findings provide a rationale for the urgent need for stringent control of air pollution to reduce PM2.5 concentration.